Enhancing Crystallization in Hybrid Perovskite Solar Cells Using Thermally Conductive 2D Boron Nitride Nanosheet Additive. Issue 15 (11th January 2023) - Yin, Yifan; Zhou, Yuchen; Fu, Shi; Zuo, Xianghao; Lin, Yu‐Chung; Wang, Likun; Xue, Yuan; Zhang, Yugang; Tsai, Esther H. R.; Hwang, Sooyeon; Kissenger, Kim; Li, Mingxing; et al.
Abstract: Controlling crystallization and grain growth is crucial for realizing highly efficient hybrid perovskite solar cells (PSCs). In this work, enhanced PSC photovoltaic performance and stability by accelerating perovskite crystallization and grain growth via 2D hexagonal boron nitride (hBN) nanosheet additives incorporated into the active perovskite layer are demonstrated. In situ X‐ray scattering and infrared thermal imaging during the perovskite annealing process revealed the highly thermally conductive hBN nanosheets promoted the phase conversion and grain growth in the perovskite layer by facilitating a more rapid and spatially uniform temperature rise within the perovskite film. Complementary structural, physicochemical, and electrical characterizations further showed that the hBN nanosheets formed a physical barrier at the perovskite grain boundaries and the interfaces with charge transport layers, passivating defects, and retarding ion migration. As a result, the power conversion efficiency of the PSC is improved from 17.4% to 19.8%, along with enhanced device stability, retaining ≈90% of the initial efficiency even after 500 h ambient air storage. The results not only highlight 2D hBN as an effective additive for PSCs but also suggest enhanced thermal transport as one of the pathways for improved PSC performance by 2D material additives in general. Abstract : In situ synchrotron X‐ray scattering and real‐time thermal imaging for the first time unraveled the effects of the thermally conductive additive, hexagonal boron nitride nanosheets, on enhancing the crystallization kinetics in organic‐inorganic hybrid perovskites and the associated solar cell performance and stability.